Mental health literacy at the public health level in lmic : supporting effective help - seeking behavior - Weiss, Bar (2020)
“Mental health literacy” refers to knowledge, beliefs, and behaviors that are supportive of positive mental health, including the ability for successful help - seeking as necessary. Development of mental health literacy can occur at two levels, the individual person le level and the public health level. The individual person level involves development of mental health literacy through (al) direct contact with (a2) specifically targeted persons (e.g. , students participating in a mental health literacy training program at their school). The public health level is broader and involves (bl) indirect contact (e.g., via television and radio ads, internet advertisements) using (62 ) general public health campaigns not targeting specific individuals (e.g., a national public health depression awareness campaign). The individual person level has the significant advantage that there is extended direct contact between the individual and the professional (s) providing the training, where detailed information can be provided with questions and uncertainties answered, in the context of a trusting professional relationship, all of which h generally enhance the e training's impact . The public health level has the advantage of being able to reach a much larger population, with fewer resources. Help seeking as part of such mental health literacy development extends beyond help - seeking per se, to the ability to find mental health services and providers that are likely to be effective Mental health literacy development is important in all countries , but is particularly important in low- and middle - income countries ( LMIC ) where mental health resources are more scarce and less developed than in high - income countries. Finding effective mental health services may be particularly challenging in LMIC, due to LMIC's significantly lower levels of mental health service development, and limited governmental oversight of health services. This paper raises a key question related to public health mental health literacy in LMIC, with a specific focus on the Southeast Asian LMIC of Vietnam : How can (a) the professional mental health community in LMIC ( b ) provide information at the broad public health level (c) regarding evidence - based mental health treatments (d) in a manner such that the general lay public believes in and understands the potential effectiveness and value of these services and their providers, vs. information regarding non - evidence - based potentially iatrogenic treatments ?